Perlindungan Hukum Terhadap Perseroan Terbatas Perusahaan Penanaman Modal Asing Neano Resort Yang Dibakar Oleh Warga Desa Bugbug di Kabupaten Karangasem - Ni Ketut Rahayu Utami Laksmidewi; I Nyoman Putu Budiartha; I.B. Gede Agustya Mahaputra (Warmadewa Press, 2025)
The principle of openness refers to the principle that the law-making process must be conducted in an open and transparent manner to the public. This means that the process must be accessible to the general public and interested parties and provide opportunities for them to participate and provide input. In a democratic society, the government should prioritize the welfare of its citizens and listen to their wishes. However, there may be differences of opinion among citizens when it comes to making laws and regulations. The problem formulations raised are 1) How is the regulation of the process of forming laws and regulations in Indonesia? and 2) How is the form of the principle of openness in the formation of laws and regulations? The research method used in this research is normative legal research. The results show that the process of forming laws and regulations in Indonesia goes through several stages, such as initiation, preparation, discussion, ratification, enactment, and implementation. The principle of openness is very important in making laws and regulations because this principle encourages public involvement in the process because it includes providing access to information and seeking input from individuals and groups affected or interested in the issue.